10^2 + 4 * (6 + 3) - 27 ÷ (9 - 6) = 127
=100 + 4 * 9 - 27 ÷ 3
multiplication & division before addition and subtraction (order of operations rules, PEMDAS)
100 + 36 - 9= 127
136 - 9= 127
127= 127
Place a set of parentheses around (6+3) and (9-6).
Hope this helps! :)
Answer is A.
√6 + √2
-----------
4
2x-7y=18 _(1)
-2x+4y=5
11y=23 , Y=23/11 sub in 1
2x-7×23/11=18
2x = 18×11 + 7×23
x = ( 198 + 161 )/2 = 359/2
Answer: lppkoijhuytfrdeswasdxcvbn
Step-by-step explanation:
Answer:
![\huge\boxed{\dfrac{f(x+h)}{h}=\dfrac{2x^2+4xh+2h^2-5}{h}}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7B%5Cdfrac%7Bf%28x%2Bh%29%7D%7Bh%7D%3D%5Cdfrac%7B2x%5E2%2B4xh%2B2h%5E2-5%7D%7Bh%7D%7D)
![\huge\boxed{\dfrac{f(x+h)}{h}=\dfrac{2x^2-5}{h}+4x+2h}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7B%5Cdfrac%7Bf%28x%2Bh%29%7D%7Bh%7D%3D%5Cdfrac%7B2x%5E2-5%7D%7Bh%7D%2B4x%2B2h%7D)
Step-by-step explanation:
![f(x)=2x^2-5\\\\\dfrac{f(x+h)}{h}=\dfrac{2(x+h)^2-5}{h}=\dfrac{2(x^2+2xh+h^2)-5}{h}\\\\\dfrac{f(x+h)}{h}=\dfrac{2x^2+4xh+2h^2-5}{h}\\\\h\neq0](https://tex.z-dn.net/?f=f%28x%29%3D2x%5E2-5%5C%5C%5C%5C%5Cdfrac%7Bf%28x%2Bh%29%7D%7Bh%7D%3D%5Cdfrac%7B2%28x%2Bh%29%5E2-5%7D%7Bh%7D%3D%5Cdfrac%7B2%28x%5E2%2B2xh%2Bh%5E2%29-5%7D%7Bh%7D%5C%5C%5C%5C%5Cdfrac%7Bf%28x%2Bh%29%7D%7Bh%7D%3D%5Cdfrac%7B2x%5E2%2B4xh%2B2h%5E2-5%7D%7Bh%7D%5C%5C%5C%5Ch%5Cneq0)